(untitled) (Advances in Applied Mathematics and Mechanics, 2022)
In this work, a non-classical analytical approach for buckling analysis of partially cracked generally orthotropic plate is proposed under the thermal domain. The derivation for the governing equation is based on the non-classical approach using Kirchhoff’s thin plate theory and the modified couple stress theory. The effect of fibre orientation on critical buckling temperature is incorporated by considering the coefficients of mutual influence. Line spring model is applied with some modifications to formulate all the crack terms while the thermal effects are introduced in form of thermal in-plane moments and forces. The final governing equation is solved using Galerkin’s method and the relation for critical buckling temperature as affected by fibre orientation is obtained. The variation of critical buckling temperature as affected by fibre orientation for different values of crack length, crack location and length scale parameter is presented. Also, the effect of fibre orientation on fundamental frequency under the thermal domain is analysed.